2018
DOI: 10.1038/s41598-018-20941-w
|View full text |Cite
|
Sign up to set email alerts
|

Value of Circulating Cytokine Profiling During Submaximal Exercise Testing in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Myalgic Encephalomyelitis or Chronic Fatigue Syndrome (ME/CFS) is a heterogeneous syndrome in which patients often experience severe fatigue and malaise following exertion. Immune and cardiovascular dysfunction have been postulated to play a role in the pathophysiology. We therefore, examined whether cytokine profiling or cardiovascular testing following exercise would differentiate patients with ME/CFS. Twenty-four ME/CFS patients were matched to 24 sedentary controls and underwent cardiovascular and circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
3
31
1
Order By: Relevance
“…myalgic encephalomyelitis/chronic fatigue syndrome | diagnostic biomarker | nanoelectronics biosensor | artificial intelligence | machine learning M yalgic encephalomyelitis/chronic fatigue syndrome (ME/ CFS) is a disease that affects at least 2 million Americans and millions more globally (1)(2)(3). Several studies have found that this disease may be triggered by a combination of factors such as major life stressors, infection (viral: ENV, HHV-6, HHV-7, stomach viruses, cytomegalovirus, and bacterial infections), toxin exposure, immunodeficiency, nutritional deficiencies, genetic susceptibility, and several others (1,4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…myalgic encephalomyelitis/chronic fatigue syndrome | diagnostic biomarker | nanoelectronics biosensor | artificial intelligence | machine learning M yalgic encephalomyelitis/chronic fatigue syndrome (ME/ CFS) is a disease that affects at least 2 million Americans and millions more globally (1)(2)(3). Several studies have found that this disease may be triggered by a combination of factors such as major life stressors, infection (viral: ENV, HHV-6, HHV-7, stomach viruses, cytomegalovirus, and bacterial infections), toxin exposure, immunodeficiency, nutritional deficiencies, genetic susceptibility, and several others (1,4,5).…”
mentioning
confidence: 99%
“…In some instances, researchers have linked cytokine profiles and inflammation to the severity of ME/CFS in patients (4). One study examined cytokine profiles postexertion to explore potential differences in ME/CFS and sedentary controls (2). Others have focused on finding physiological anomalies by looking at exercise intolerance and cardiac impairment (2,22).…”
mentioning
confidence: 99%
“…This interaction between symptom severity and duration of illness has not been explored in the literature. Some studies have reported data on duration of illness [6,51] or stipulated an illness duration in their inclusion criteria [8,36,54], and others assessed fatigue severity [3,14,17,31] or symptom severity [8,22,35,42,50,51,54]. Only one study in this review reported data on both symptom severity and illness duration [51].…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, molecular biomarkers have been pursued across multiple areas of research. For example, the role of the immune system in ME/CFS has been studied for decades, raising cytokines as potential biomarkers of disease [8][9][10][11][12][13][14] whose clinical utility would be aided by their accessibility in blood. Other cytokine studies have utilised cerebrospinal fluid [15,16], the acquisition of which is more invasive than drawing blood, and so could be less amenable to a routine diagnostic test.…”
Section: Introductionmentioning
confidence: 99%